2022
DOI: 10.1177/2333794x221078700
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis of Lifestyle and Household Environment for Toddlers With Symptoms of Acute Respiratory Infection (ARI) in Indonesia in 2007, 2012, and 2017

Abstract: Introduction. The morbidity and mortality rate of Acute Respiratory Tract Infection (ARI) in children under 5 is relatively high in Indonesia. Socio-demographic characteristic is considered one of the factors causing ARI in Indonesia. However, no study analyzed the prevalence of ARI among toddlers and the differences among the determinant factors in multiple periods. Thus, this study aimed to analyze the prevalence trends and determinant factors associated with ARI symptoms in children under 5 in Indonesia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…DHS 2017 data showed that ARI in the Philippines (1.51%) was lower than in Indonesia (4.22%). However, previous studies showed that the percentage of ARI in toddlers was 5.7% in 2013 in the Philippines [ 14 ] and 5.12% in 2012 in Indonesia [ 20 ]. It can be concluded that the number of ARI cases in under-five children is much lower in the Philippines compared to Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…DHS 2017 data showed that ARI in the Philippines (1.51%) was lower than in Indonesia (4.22%). However, previous studies showed that the percentage of ARI in toddlers was 5.7% in 2013 in the Philippines [ 14 ] and 5.12% in 2012 in Indonesia [ 20 ]. It can be concluded that the number of ARI cases in under-five children is much lower in the Philippines compared to Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the percentage of children under five years of age experiencing ARI in 2018 was 12.8 percent, with the highest percentage in the province of East Nusa Tenggara [9]. Morbidity and mortality caused by ARI in Indonesia are still relatively high and become a health problem [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, 2012, and 2017 there has been a downward trend in the prevalence of factors associated with ARI symptoms in children under five years of age in Indonesia [10]. However, community awareness about the dangers of ARI still needs to be considered because research showed that children aged two years or over two years old are less likely to seek health care when they have symptoms of ARI compared with children less than two years of age with ARI symptoms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the SSA region and other emerging economies have observed a correlation between ARIs and age, 7 , 11 - 13 sex, 12 , 14 immunization status, 12 HIV infection, 3 diarrheal comorbidity, 2 , 14 malnutrition 14 , 15 and improper weaning timing. 15 Several research has demonstrated the association between parental characteristics and ARIs, including parent age, 13 , 16 - 18 work status 12 and educational level. 3 , 12 Other variables have been implicated to an elevated risk of ARIs, such as socioeconomic status, 11 , 15 home type 18 and household size, as well as lack of hygiene and sanitation facilities, 17 have been linked with increased risk of ARIs.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers in the household, type of fuel used for cooking, poor drinking water quality, and lack of toilets are some examples of lifestyle and environmental factors that increase the risk of developing ARIs. 3 , 15 , 17 …”
Section: Introductionmentioning
confidence: 99%